LIPOPROTEIN (A) LEVELS AND RISK OF CARDIOVASCULAR DISEASES AMONG INDIVIDUALS WITH SUBCLINICAL HYPOTHYROIDISM - MOHAMMED, NOORA ABDULJALEEL (Fırat Üniveristesi, 2021)
Bu alanda yazı stili değişikliği yapılmamalıdır. Gerek duyulması halinde Stil Galerisinden "Özet Metni" stili kullanılmalıdır. Yazı büyüklüğü 10 punto ve 1,25 aralık ayarlıdır. Paragraf başları (ilk satır) 1 cm sol girinti ile başlar. Paragraflar arasında ayrıca boşluk bulunmaz. İlk 1-2 cümlede konunun önemi ve tezin amacı tanımlanmalı, 1-2 cümle ile tezin hipotezleri açıkça verilmeli, 1-2 cümlede örneklem ve örneklem büyüklüğü belirtilmeli, 1-2 cümle ile yöntem hakkında bilgilendirme yapılmalı, birkaç cümle ile bulgular hakkında kısa bilgiler sunulmalıdır. Son olarak üretilen bilgi kısaca ifade edilmelidir. Özetin altında, konuyu tanımlayan anahtar kelimeler bulunmalıdır. En az 3 (üç) en fazla 6 (altı) anahtar kelime kullanılır. Özet ve Abstract sayfası 250 kelime ile sınırlandırılmalı, kaynak gösterimi, şekil, tablo ve denklem gibi öğeler bulundurmamalıdır. Mümkün oldukça üst ya da alt simge ve Yunan harfleri gibi semboller kullanılmamalıdır. Özetin 250 kelimeyi aşan kısımları Ulusal Tez Veri Merkezinde saklanmaz. Her hâlükârda özet ve anahtar kelimeler bir sayfa ile sınırlandırılmalıdır. Bir sayfayı aşan özet ve anahtar kelimeler Enstitü tarafından kabul edilmez.

Background: Subclinical hypothyroidism (SCH) is the mildest type of thyroid hormone deficiency and can have adverse effects. It is important to identify patients with subclinical hypothyroidism that has an elevated cardiovascular risk (CVR). The aim of the study was to evaluate Lp (a) value as a cardiovascular risk factor among patients with subclinical hypothyroidism. Materials and Methods: The study included 50 patients newly diagnosed with SCH and 50 healthy controls matched by age and gender. Cobas 6000 was used to analyze the parameters. Results: In subclinical hypothyroidism patients, serum Lp (a), total cholesterol (TC) 152.98 (26.25), and low-density lipoprotein cholesterol (LDL-C) levels 96.54 (24.72) were significantly higher compared to healthy control. In addition, a significant positive association was found for subjects with subclinical hypothyroidism between TSH and anti-TPO (0.489), TC (0.311). However, Lp (a)(0.073), LDL-C (0.278), TG (0.28) levels, showed no significant positive correlation with the levels of TSH. Further more Lp (a) in patient with subclinical hypothyroidism has a significant correlation with APOB (0.407), LDL (0.309), TC (0.314). Conclusion: We concluded that there was an increased concentration of certain CVR variables in SCH patients. The possible benefits could be preventing progression to overt hypothyroidism and initiating adequate therapy to improve lipid parameters.
Keywords: Kimya